The Relevance of Al-Umm Madrasatul Ula for Career Mothers in the 21st Century (EDUKASIA, 2025)
The rapid development of the times has caused many shifts in parenting styles, especially for a woman as a mother. The increasing demands of the current era force women in hard position in reconciling work and family. The situation impacted child-rearing behavior and the overall quality of family life. This study aimed to determine the relevance of al-umm madrasatul ula in the case of career mothers and analyze their role in forming the religious character of children aged eight to nine years old. This study employed a quantitative survey method using a semantic differential scale by Osgood questionnaire distributed to 33 career mothers of students at SD Islam Surya Buana Malang, with data was analyzed trough descriptive statistics. The results showed that 88 percent of mothers still doing their obligations as al-umm madrasatul ula depend on al-Maghribi’s and al-Ghazali’s perspectives even though they played dual roles as housewives and working mothers.